Benzodiazepine dependence and its treatment with low dose flumazenil. (February 2014) - Hood, Sean David; Norman, Amanda; Hince, Dana Adelle; Melichar, Jan Krzysztof; Hulse, Gary Kenneth
<x xml:space="preserve">Abstract</x> Globally benzodiazepines remain one of the most prescribed medication groups, especially in the primary care setting. With such high levels of prescribing it is not surprising that benzodiazepine dependence is common, cutting across all socioeconomic levels. Despite recognition of the potential for the development of iatrogenic dependence and the lack of any effective treatment, benzodiazepines continue to be widely prescribed in general practice. Conventional dependence management, benzodiazepine tapering, is commonly a protracted process over several weeks or months. It is often associated with significant withdrawal symptoms and craving leading to patient drop out and return to use. Accordingly, there is a worldwide need to find effective pharmacotherapeutic interventions for benzodiazepine dependence. One drug of increasing interest is the GABAA benzodiazepine receptor antagonist/partial agonist, flumazenil. Multiple bolus intravenous infusions of low dose flumazenil used either with or without benzodiazepine tapering can reduce withdrawal sequelae, and/or longer term symptoms in the months following withdrawal. Preliminary data suggest that continuous intravenous or subcutaneous flumazenil infusion for 4 days significantly reduces acute benzodiazepine withdrawal sequelae. The subcutaneous infusion was shown to be tissue compatible so the development of a longer acting (i.e. several weeks) depot flumazenil formulation has been explored. This could be capable of managing both acute and longer term benzodiazepine withdrawal sequelae. Preliminary in vitro water bath and in vivo biocompatibility data in sheep show that such an implant is feasible and so is likely to be used in clinical trials in the near future.